ANALYSIS OF PERSONNEL CAPABILITY GAP IN COVERING VACANT POSITION OF D&C OPERATION PT. SOG (The Indonesian Journal of Business Administration, 2019)
This research aims to help D&C to evaluate DWSM consultant role that currently substitute employee role in operation. This research will first figure out non-satisfaction aspect of consultants in D&C. It is found that the user is not satisfy regarding consultant performance. Problem analysis is conducted using 5 Whys to gain better understanding regarding the root cause of the problem, which recommend to conduct assessment of capability that required for DWSM vacant position. Capability Based Assessment is conducted to address un-ideal condition of current consultant performance toward D&C expectation. Using Capability Based Assessment (CBA), this research concludes there are 12 capability gaps between current Consultant and D&C standard. By having these gaps, it means D&C currently facing lack of capable personnel for the position. To generate recommendation to fill the gaps in order to get capable personnel, this research will use HCM value matrix framework. Each capability gap will be categorized based on its “level of value” provided. Found out that the gaps are in the “added value” which represents capabilities that required to meet business needs. This value level becomes a basis to generate input in HCM value chain that led to the “input” for what the team really needs to do to fill the gaps. Finally, using HCM Value Matrix is it generated that the D&C Operation needs to develop talent pool by hiring new employee and apply “the learning organization” to get the talent into expected capability level.Keywords: assessment, capability, human capital, management, performance